Internet of things-based services implementation and challenges in malaysia: A review - Sidek N.; Ali N. (Science and Engineering Research Support Society, 2023)
The fields of electronics and computer science have merged to form one of the most significant technological advances; the Internet of Things (IoT). IoT has become a key trend all over the world. Although still in its early stage of development, the impact of IoT in Malaysia has been significant. However, there exist particular challenges in achieving successful implementation of IoT-based services. This paper aims to review and understand the implementation status of IoT-based services in Malaysia. The challenges, as well as suggestions for future research trends, are discussed. 2019 SERSC.